Studi Analisis Terhadap Kasus Pelengseran Presiden Mesir dalam Pemberitaan Surat Kabar al-Masry al-Youm: Perspektif Model Teeun Van Dijk - Isniyatun Nizwah MZ (Menara Tebuireng, 2018)
This research is a study of critical discourse analysis that discusses about the discourse of the overthrow of Muhammad Mursi and his support groups in the online newspaper al-Mas}ry al-Youm. This study has a purpose examine the macro structure and super structure in the discourse stated by newspaper letters, then examine the style of language used by news makers. In this study, data was obtained from www. Al-Masry al-Youm, the focus on June and July in 2013. This study uses Van Dijk's theory of critical discourse analysis to dissect data. This research only take three steps from van Dijk's theory, namely macro structure, super structure and micro structure. This study uses descriptive-qualitative methods, at where there are three stages carried out by researchers, including: first, data collection stage, researchers used the method refer to the technique see free conversations with newspapers. Second, analyze data with using the Agih method so that data can be classified and then analyzed by using the theory of critical discourse analysis initiated by Teeun A. Van Dijk. Third, the provision of data presented using language commonly used in research. The results of the research obtained are: first, from the macro structure indicates that Muhammad Mursi and his support groups constitute marginalized groups, so the big theme in the newspaper is in the form of vices carried out by Muhammad Mursi and his group. Second, from the super structure shows that discourses are built by reporters showing opposition to Muhammad Mursi along with him his group, and the image was built on the military council. Third, on aspects language style, found vocabulary containing negative elements inside pronounce Mursi and his group, and vice versa, vocabulary is used which contains positive elements when making a statement about the military council along with the support group. Then our pronouns are used when mentioning the name Abdul Fatah el-Sisi (Commander of the Armed Forces) and people. From the analysis of the data above, it can be seen that the newspaper al-Masry al-Youm has a bias towards the Egyptian military council and opponents Muhammad Mursi and his group of followers